In vitro Modified Release Studies on Melatoninergic Fluorinated Phenylalkylamides: Circumventing their Lipophilicity for Oral Administration - Vlachou, Marilena; Siamidi, Angeliki; Protopapa, Chrystalla; Vlachos, Michalis; Kloutsou, Sophia; Dreliozi, Chrysoula-Christina; Papanastasiou, Ioannis P. (Current Pharmaceutical Design, 2024)
Introduction: In an attempt to circumvent the lipophilicity burden for the oral administration of new potent synthetic melatoninergic fluorine-substituted methoxyphenylalkyl amides, we conducted in vitro modified release studies using carefully selected matrix tablets’ biopolymeric materials in different ratios. Methods: In particular, we sought to attain release profiles of these analogues similar to that of the parent compound, the chronobiotic hormone Melatonin (MLT), and also of the commercially available drug, Circadin®. Results: It was found that some of these systems, albeit being more lipophilic than MLT, mimic the in vitro release patterns of melatonin and Circadin®. Conclusion: Moreover, a number of these derivatives were proven suitable for dealing with sleep onset problems, whilst others for dealing with combined sleep onset/sleep maintenance dysfunctions.
Keywords: matrix tablets